MODEL HUBUNGAN KOMPETENSI, INDEPENDENSI, PROFESIONALISME DAN KUALITAS AUDIT SERTA DAMPAKNYA TERHADAP KEMAMPUAN MENDETEKSI FRAUDS - Wirmie Eka Putra; Indra Lila Kusuma; Maya Widyana Dewi (ITB AAS INDONESIA, 2022)
This study entitled the influence of competency, independency, professionalism on ability to detect fraud with audit quality as an intervening variable, aims to examine the influence of competency, independency, professionalism, on audit quality and ability to detect fraud, and also examine the mediating effect of audit quality. The sample used in this study was all the member of Bungo and Tebo Regency’s inspectorate with total 28 respondents. The data analysis techniques used in this sstudy were descriptive statistics and path analysis used SmartPLS 3 software. The results of this study are: competency, independency, and professionalism partially influence audit quality, while only competency, professionalism, and audit quality influence the ability to detect fraud. There are no evidence that audit quality mediating the influence of competency, independency, and professionalism on ability to detect fraud.